Quels prélèvements aux urgences pour le diagnostic microbiologique d’une infection pulmonaire communautaire grave du sujet immunocompétent ? - Thellier, D. (Reanimation, 2014)
Current diagnostic methods allow microbial identification in 50% of patients admitted with severe community-acquired pneumonia (CAP). Guidelines derived from epidemiological data help physicians to start empirical antimicrobial therapy. Definitive microbial diagnosis is useful to guide further pathogen-directed therapy. Blood cultures, cultures of respiratory specimens and urine antigen tests are recommended to determine the causative bacterial pathogen. Positive blood cultures range from 15 to 25% of CAP patients according to severity. Whether sputum specimens represent or not lower respiratory secretions determines its accuracy in CAP microbial diagnosis. In intubated patients, endotracheal aspirates are often of interest. Detection of positive pneumococcal or legionella urinary antigen is often associated with CAP severity. The sensitivity of this test is not decreased in patients who have received antibiotics prior to sampling. Viral pneumonia account for 10 to 40% of severe CAP. Nasal swabs are recommended for influenza identification using polymerase chain reaction (PCR) in order to deliver oseltamivir treatment. In the emergency department, atypical pneumonia serology is less useful than respiratory specimens obtained using fiberoptic bronchoscopy. Serum PCR to diagnose bacterial CAP is not superior to the other usual methods.